Protocol for a systematic review on routine use of antibiotics for infants less than 6 months of age with growth failure/faltering - Jai K Das; Zulfiqar Ahmed Bhutta; Abigail Smith; Aamer Imdad; Emily Tanner-Smith; Melissa François; Fanny F Chen; Olivia J Tsistinas (BMJ Open)
Introduction Antibiotics have been used as an adjunct in treating children with severe acute malnutrition 6–59 months of age; however, the data for infants less than 6 months are scarce. The WHO recently started guideline development for preventing and treating wasting, including growth failure/faltering in infants less than 6 months. This systematic review commissioned by WHO aims to synthesise evidence from current literature on the effectiveness of antibiotics for infants less than 6 months of age with growth failure/faltering.Methods and analysis We will conduct a systematic review and meta-analysis for studies that assessed the effect of antibiotics in the treatment of infants with growth faltering. We will search multiple electronic databases. We will include randomised control trials and non-randomised studies with a control arm. The study population is infants less than 6 months of age with growth failure. The intervention group will be infants who received no antibiotics or antibiotics other than recommended in 2013 guidelines by WHO to treat severe acute malnutrition in children. The comparison group will be infants who received antibiotics according to the 2013 guideline by WHO. We will consider the following outcomes: mortality, clinical deterioration, antimicrobial resistance, recovery from comorbidity, adverse events, markers of intestinal inflammation, markers of systemic inflammation, hospital-acquired infections, non-response. We will use the meta-analysis to pool the studies where applicable. We will use the Grading of Recommendations Assessment, Development, and Evaluation approach to reporting the overall evidence quality for an outcome.Ethics and dissemination This is a systematic review and will not involve contact with a human subject. The findings of this review will be published in a peer-review journal and will guide the WHO’s recommendation for the use of antibiotics in infants less than 6 months of age with growth failure.PROSPERO registration number CRD42021277073.